فعالية التدقيق المالي على تحليل القوائم المالية - محمدي, ايمان (My University, 2021)
The analysis of Financial statements is considered one of the Most important operations carried out by the institution, as it provides it with financial information that helps it to make the right decisions. However, this information can not be trusted unless it is approved by a neutral party. This note deals with the effectiveness of financial auditing on the analysis of financial statements. Thus, to the conceptual Framework of the financial audit, followed by the financial audit practices and their relationship to the analysis of the financial statement. The theoretical aspect was also dropped through the field study, the office of the accounts governor of the state of Mostaganem, where we found that the financial audit is of great importance in the analysis of the financial statements, by imparting quality and transparency to the financial statements.
مكتب محافظ الحسابات
Keywords: Financial auditing, financial statements, accounts governor